Epilog burzy Zbigniewa Herberta (na marginesie kerygmatycznej interpretacji Przesłania pana Cogito) - Peroń, Małgorzata (Colloquia Litteraria, 2014)
Zbigniew Herbert’s Epilogue to a Storm (on the margins of a kerygmatic interpretation of Last Message from Mr. Cogito) Zbigniew Herbert’s Epilogue to a Storm, last volume by the poet, sets the perspective of a finish and a finale. Death and different ways of getting closer to what is beyond death is one of the leading subjects of the volume. Marian Maciejewski created main interpretative tropes in Herbert’s poetry; they are related to the topos of ‘fear of death’ and the ‘autosalvation’ stance that defines the protagonist of Last Message from Mr. Cogito. One can see in Epilogue to a Storm a number of ways of ‘exorcising time’ put forward by the researcher: instances of going back to childhood, memories of hometown, registration of ‘the moment’. Reflections on death take place on two levels: horizontal and vertical. The former symbolises life understood as journey, and its basic image is water. The latter is linked to halt and profoundness, which refer to death and eternity (the Brewiarz cycle).